The phytochemistry of Cymbopogon winterianus essential oil from Lombok Island, Indonesia and its antifungal activity against phytopathogenic fungi - PUTRI SRI ANDILA; I PUTU AGUS HENDRA; PUTRI KESUMA WARDANI; I GEDE TIRTA; SUTOMO SUTOMO; DEDEN FARDENAN (Smujo International, 2018)
Andila PS, Hendra IPA, Wardani PK, Tirta IG, Sutomo, Fardenan D. 2018. The phytochemistry of Cymbopogon winterianus essential oil from Lombok Island, Indonesia and its antifungal activity against phytopathogenic fungi. Nusantara Bioscience 10: 232-239. Cymbopogon winterianus Jowitt ex Bor [Sereh Wangi] is a plant producing essential oil that has been extensively used in perfumery, mosquito repellent, medicinal, and cosmetic industry. In Indonesia, the accession of C. winterianus plant had been collected from natural forest in Sembalun, Lombok, West Nusa Tenggara (NTB) Province. However, the phytochemical properties and its biological potential of this accession have never been reported. The aim of this study was to determine the phytochemical content of essential oil of C. winterianus from Lombok and to explore its potential as a bioantifungal against several phytopathogen fungi. The essential oils were extracted from fresh stem and leaf of C. winterianus by hydrodistillation. The chemical composition of them was determined by chromatography-mass spectrometry (GC-MS). A total of 26 and 20 compounds were obtained from the stem and leaf oil with the dominant compounds of essential oil in stem were Torreyol (17.89%), Oxirane, octyl- (15.84%), (-)-Isopulegol (14.44%), Isopulegol 2 (12.18%), and Geranyl Acetate (5.89%) while in leaf were (-)-Isopulegol (22.69%), Oxirane, octyl- (16.64%), Cyclohexanol, 5-methyl-2-(1-methylethenyl)- (14.21%),